2016
DOI: 10.1080/17470218.2016.1146780
|View full text |Cite
|
Sign up to set email alerts
|

The “Parts and Wholes” of Face Recognition: A Review of the Literature

Abstract: It has been claimed that faces are recognized as a “whole” rather than the recognition of individual parts. In a paper published in the Quarterly Journal of Experimental Psychology in 1993, Martha Farah and I attempted to operationalize the holistic claim using the part/whole task. In this task, participants studied a face and then their memory presented in isolation and in the whole face. Consistent with the holistic view, recognition of the part was superior when tested in the whole-face condition compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
138
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(150 citation statements)
references
References 90 publications
11
138
0
1
Order By: Relevance
“…Behaviorally, we excel at distinguishing these different sources of information, and can easily identify a familiar person just from their face despite changes in expression or viewpoint. Indeed, the processing of faces has been suggested to be 'special' (Richler & Gauthier, 2014), and faces have been proposed to be processed more holistically than other visual stimuli (Shen & Palmeri, 2015;Tanaka & Simonyi, 2016; but see also Gold, Mundy, & Tjan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Behaviorally, we excel at distinguishing these different sources of information, and can easily identify a familiar person just from their face despite changes in expression or viewpoint. Indeed, the processing of faces has been suggested to be 'special' (Richler & Gauthier, 2014), and faces have been proposed to be processed more holistically than other visual stimuli (Shen & Palmeri, 2015;Tanaka & Simonyi, 2016; but see also Gold, Mundy, & Tjan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This effect is commonly cited as evidence of non-analytic, holistic or configural processing, whereby the images are recognized as a whole, by gleaning the relational or covariant visual structure among constitute features, rather than part-by-part or by a general perceptual process [23]. The opposite appears to be the case, however, with unfamiliar face matching examiners, suggesting they may rely less on configural processing than in domains where the objects or categories are familiar.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work examined the effects of alcohol intoxication on the accuracy of retrospective confidence judgments in face recognition (e.g., Flowe et al, ; Kneller & Harvey, ; Yuille & Tollestrup, ), and one study found that intoxication impaired the accuracy of prospective JOLs for word pairs (Nelson et al, ). However, it cannot be assumed that such results would translate to prospective JOLs in face recognition, due to differences between memory for faces and words (e.g., Tanaka & Simonyi, ), and in the cues that affect JOLs versus retrospective confidence (e.g., Rhodes, ).…”
Section: Discussionmentioning
confidence: 99%
“…These results provide some evidence that alcohol might impair metacognitive judgments made soon after acquiring new memorial information. However, given the differences in processing of faces versus word pairs (e.g., Maurer, Le Grand, & Mondloch, ; Tanaka & Simonyi, ), it cannot be assumed that the effects of alcohol on JOLs found by Nelson et al () will translate to a face recognition task.…”
Section: Effects Of Alcohol Intoxication On Metacognitionmentioning
confidence: 99%